2018
DOI: 10.4172/2157-7471.1000432
|View full text |Cite
|
Sign up to set email alerts
|

Non-Dependency of In Vitro Fungicidal Efficiency of Copper Nanoparticles against Fusarium oxysporum upon Particle Size

Abstract: Although many papers have consented that the smaller the size of nanoparticles, the higher their efficiency, this paper sheds light on one potential exception of this rule. The paper shows that the in vitro antifungal efficiency of copper nanoparticles against the fusarium wilt pathogen, Fusarium oxysporum, isolated from the infected date palm, Phoenix dactylifera L., is not size-dependent; instead, as it was found that larger copper nanoparticles have better in vitro antifungal efficiency against the fungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Among various types of nanoparticles, copper and copper oxide nanoparticles attract much attention because of their distinguished catalytic, mechanical, magnetic, electric and thermal properties; in addition to their versatile applicability in many fields including agricultural, industrial, environmental and medical applications [2]. Furthermore, copper and copper oxide nanoparticles can be used in catalysis [3], sensors [4], degradation of dyes [5], fungicidal [6,7] and nematicidal [8] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of nanoparticles, copper and copper oxide nanoparticles attract much attention because of their distinguished catalytic, mechanical, magnetic, electric and thermal properties; in addition to their versatile applicability in many fields including agricultural, industrial, environmental and medical applications [2]. Furthermore, copper and copper oxide nanoparticles can be used in catalysis [3], sensors [4], degradation of dyes [5], fungicidal [6,7] and nematicidal [8] applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different susceptibility of the above fungal species in the tested concentrations showed that the efficient dose and incubation time influence the maximum outcome in fungal growth inhibition [ 82 , 83 ]. Much bigger sizes of Cu NPs (345.1 nm) with polygonal shapes showed better antifungal efficiency (46%) against Fusarium oxysporum compared to spherical-shaped Cu NPs (278.1 nm) at the same concentration [ 84 ]. The polygonal shape exhibits a larger surface area to volume ratio, contributing to the antifungal efficiency.…”
Section: Favored Inpsmentioning
confidence: 99%
“…The polygonal shape exhibits a larger surface area to volume ratio, contributing to the antifungal efficiency. The large size of Cu NPs, comparable to the targeted fungus entities, was considered as increasing the probability of an effect [ 84 ].…”
Section: Favored Inpsmentioning
confidence: 99%
“…In particular, nanostructured Cu films possess distinctive mechanical, thermal, magnetic, electric and catalytic properties, which make them suitable for application in many fields such as industry, medicine, and the environment [29]. Furthermore, Cu thin films could be used in solar cells [30], diodes [31], catalysis [32], high-speed integrated circuits [33,34], sensors [35], fungicidal and nematicidal applications [36][37][38], etc. The grain size control of nanostructured Cu thin films and its effect on physical properties are very important for electronic applications [39], since the deposition process of semiconductors determines the grain size-band gap dependence [40].…”
Section: Introductionmentioning
confidence: 99%